2012
DOI: 10.1371/journal.pone.0033711
|View full text |Cite
|
Sign up to set email alerts
|

Hiwi Mediated Tumorigenesis Is Associated with DNA Hypermethylation

Abstract: Expression of Piwi proteins is confined to early development and stem cells during which they suppress transposon migration via DNA methylation to ensure genomic stability. Piwi's genomic protective function conflicts with reports that its human ortholog, Hiwi, is expressed in numerous cancers and prognosticates shorter survival. However, the role of Hiwi in tumorigenesis has not been examined. Here we demonstrate that (1) over-expressing Hiwi in sarcoma precursors inhibits their differentiation in vitro and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…Ts-3676 methylation state and possibly provide sequence specificity for DNA methylation (14,15). Because of the similarity of tsRNAs to piRNAs, we hypothesized and then proved that these molecules can interact with Piwi proteins (24).…”
Section: Ts-4521mentioning
confidence: 95%
See 1 more Smart Citation
“…Ts-3676 methylation state and possibly provide sequence specificity for DNA methylation (14,15). Because of the similarity of tsRNAs to piRNAs, we hypothesized and then proved that these molecules can interact with Piwi proteins (24).…”
Section: Ts-4521mentioning
confidence: 95%
“…Although miRNAs are created through a double-stranded precursor molecule (12), piRNAs biogenesis involves long single-stranded precursor molecules (11). PiRNAs interact with Piwi proteins and appear to cooperate with DNA methyltransferases to affect methylation of genes, suggesting that Piwi/piRNAs complexes are global regulators of chromatin state (14,15). A few years ago, a new class of small RNAs was reported to derive from tRNAs as a consequence of tRNA processing (16).…”
mentioning
confidence: 99%
“…Moreover, recent data suggested that Hiwi gene was required to maintain the stemness of hematopoietic stem cells (Sharma et al, 2001). Thus it was proposed that Hiwi gene may be a key regulator in maintenance of cancer stem cell populations as well (Taubert et al, 2007;Siddiqi et al, 2012).…”
Section: Hiwi Knockdown Inhibits the Growth Of Lung Cancer In Nude Micementioning
confidence: 99%
“…Therefore, it is not surprising that HiWi has been implicated in oncogenesis. Several studies have demonstrated that HiWi is expressed in tumor tissues, and is one of the most important elements in the regulation of cancer cells (8,9). HIWI was also correlated with patient prognosis in pancreatic, colon, colorectal, lung, and endometrial cancer (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%